Determinants of Socio-Demographic Characteristics on Financial Inclusion of Women in Mataram City and West Lombok Regency - Taufiq Chaidir; Muaidy Yasin; Jalaludin Jalaludin; Gst Ayu Arini (Publikasi Indonesia, 2024)
The objective of this research is to demonstrate that various social factors, including education, employment status, and proximity to financial service locations, along with demographic factors such as age, marital status, number of family members, and number of family members who are employed, play a crucial role in determining the level of financial inclusion in Mataram City and West Lombok Regency. The research adopts a quantitative approach and falls under the category of explanatory research. Mataram City has six sub-districts (urban locality), and West Lombok Regency has ten sub-districts (rural locality). In this study, the sample was selected using a non-probability sampling technique, which was determined purposively. The number of samples is 200 women. Procedures and models for evaluation and testing hypotheses used Structural Equation Models (SEM) and Partial Least Squares (PLS). The coefficient of determination of the structural model (R2) and the adjusted R square value (Adj R2) are 0.1840 and 0.1670, respectively. The effect-size value (f2) is more than 0.02, namely 0.192 for social characteristics and 0.093 for demographic characteristics. The results of testing hypothesis 1 (H1) concluded that social characteristics do not significantly affect the financial inclusion of women while testing hypothesis 2 (H2) concluded that demographic characteristics significantly affect the financial inclusion of women in Mataram City and West Lombok Regency. It is recommended to the monetary authority that financial service offices and ATM outlets be closer and more easily accessible to the community.